Pediatric head and neck rhabdomyosarcoma; the role of MRI in differentiation from other common pediatric malignant head and neck tumors - Parlak, Şafak; Gümeler, Ekim; Bulut, Elif (The Turkish Journal of Pediatrics, 2022)
Background. The tumor localization/extent and imaging characteristics of rhabdomyosarcomas (RMSs) especially parameningeal type, could overlap with the common tumors of the head and neck (H&N) such as lymphoma and nasopharyngeal carcinoma (NPC). Our goal was to investigate magnetic resonance imaging (MRI) features that could favor the diagnosis of RMS over lymphoma and NPC in H&N region. Methods. Pretreatment MRI of 42 pediatric patients (mean: 9.7±5.1 years, min-max: 2-18 years) with a recent diagnosis of RMS (n=12), lymphoma (n=14) and NPC (n=16) were retrospectively studied. Tumor localization, extension and spread were evaluated. Signal and enhancement characteristics of the tumors and the presence of necrosis were noted. ADC values were measured by using both the small sample and single slice methods. For comparison of three groups, the Kruskal Wallis test and Pairwise comparisons were used. The intra-class correlation coefficient (ICC) was calculated for the assessment of inter-observer agreement. Results. Nasopharynx ±parapharyngeal space involvement was detected in 58.3% of RMSs. Rhabdomyosarcoma was more heterogeneous in T2 images compared to lymphoma (p=0.014). Rhabdomyosarcoma showed significantly higher frequency of heterogeneous enhancement (p < 0.001) and necrosis (p < 0.001) among these tumors. The mean ADC values of lymphoma were significantly lower than the values of RMS (p < 0.001) and NPC (p < 0.01) for both observers. The mean ADC values were higher in RMSs than NPCs (p > 0.05). Intra-class correlation in ADC measurements was higher for the single slice method (ICC=0.997) than the small sample method (ICC=0.989). Conclusions. Rhabdomyosarcoma tends to have higher ADC values than lymphoma and has a higher frequency of heterogeneous enhancement and necrotic parts than both lymphoma and nasopharyngeal carcinoma. These features could help radiologists to differentiate RMS from the above-mentioned mimickers.
Keywords: diffusion-weighted imaging; lymphoma; magnetic resonance imaging; nasopharyngeal carcinoma; rhabdomyosarcoma